Micro-shear bond strength of different adhesives to human dental enamel - Nagayassu, M. P. [UNESP]; Shintome, L. K. [UNESP]; Arana-Chavez, V. E.; Fava, M. [UNESP] (MRE Press, 2011)
The aim of this study was to evaluate the micro-shear bond strength of 5 adhesive systems to enamel, one single-bottle acid-etch adhesive (O), two self-etching primers (P) and two all-in-one self-etching adhesives (S). Method: Sixty premolar enamel surfaces (buccal or lingual) were ground flat with 400- and 600-grit SiC papers and randomly divided into 5 groups (n=12), according to the adhesive system: SB2 - Single Bond 2 (O); CSE - Clearfil SE Bond (P); ADS - AdheSE (P); PLP - Adper Prompt L-Pop (S); XE3 - Xeno III (S). Tygon tubing (inner diameter of 0.8mm) restricted the bonding area to obtain the resin composite (Z250) cylinders. After storage in distilled water at 37°C for 24h and thermocycling, micro-shear testing was performed (crosshead speed of 0.5mm/min). Data were submitted to one-way ANOVA and Tukey test (a=5%). Samples were also subjected to stereomicroscopic and SEM evaluations after micro-shear testing. Mean bond strength values (MPa±SD) and the results of Tukey test were: SB2: 36.36(±3.34)a; ADS: 33.03(±7.83)a; XE3: 32.76(±5.61)a; CSE: 30.61(±6.68)a; PLP: 22.17(±6.05)b. Groups with the same letter were not statistically different. It can be concluded that no significant difference was there between SB2, ADS, XE3 and CSE, in spite of different etching patterns of these adhesives. Only PLP presented statistically lower bond strengths compared with others.